Reforms and Cooperation in Investment of Indo Asean: Challenges in Indo-Asean Cooperation and Investment (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The plan includes activities such as the dissemination and exchange of information, trade infrastructure, other aspects of trade facilitation and policy recommendations on trade liberalization. ASEAN and India concurred that cooperation in tourism had great potential and agreed to commission a study on India's tourism profile from ASEAN'S perspective as well as ASEAN's tourism profile from India's perspective. In October-November 1995, ASEAN and India exchanged visits of tour operators selling out-bound travel packages in a project financed by the ASEAN-India Fund. It is obvious that prevalence of instability, chaos and insecurity as well as development of communism or the continuance of colonialism in South East Asia would make difficult for India to function peacefully and achieve her goals at home or abroad. Since colonialism in South East Asia was coming to end and communism on the contrary was becoming a virulent force which by its militant character was to upset not only the stability in the region but even created a situation unfavourable to India's development also.